Effect Of Use Of Learning Media Digital In Improving Motivation Student Learning In Subjects Civics - Roulina Simanjuntak; Kondios M.D Pasaribu; Lukman Pardede; Hotmaida simanjuntak; Rince Marpaung (STABN RADEN WIJAYA WONOGIRI, 2020)
This study aims to determine the influence of digital media in learning Pancasila and Citizenship Education to improve the learning motivation of class VIII students of SMP Methodist 7 Medan. This type of research uses quantitative descriptive research. According to Sugiono (2017: 13) that the quantitative method is research that has research in the form of numbers and analysis using statistics. Because this research is in the form of quantitative descriptive, the author only describes. The research design used in this study is a post-test. All members have an equal opportunity to be research samples. Based on the results of the study and discussion, it is concluded that there is an influence of digital media on increasing student learning motivation in PPKn subjects. This is proven by the average experimental class of 74.17 and the control class 63.17. The percentage of student completion in the experimental class showed 4.17% which is greater than the control class with a percentage of 50%. This shows that the success of learning in the experimental class is greater than the control class